(untitled) (International Journal of Food and Nutritional Sciences, 2022)
GST is a new tax system which is moving towards an effective indirect tax system. More than 150 countries have introduced virtually everything at the single rate. The Goods and service tax or GST bill officially known as The constitution (One Hundred and Twenty Second Amendment) Bill 2014, proposed a National Value Added Tax and implemented in India on 1st July 2017. GST simplifies the complex indirect taxation system in India and creates a common national market. GST is a comprehensive indirect tax levy on manufactures, sales and consumption of goods and services at the national level. Our society has different opinion, reaction and different arguments against this new tax regime. India has more or less impacted every major and minor business sector in the country while some industries are seeing growth as a result of decreased taxes some others are facing a decrease in sale because of increased taxes. The Retail sector plays a major role in the economic development of the nation. Retailers like any other entity with the supply of goods and services are subject to GST when there turnover exceed 20 Lakhs. It is mandatory by law for such retailers to be registered under the GST. This study was conducted to know about the Attitude of Retailers towards GST, values of GST, willingness of implementation of GST in Kanyakumari District. The data for the study was collected by means of structured questionnaires with the sample of 50 respondents. The outcome of the study could not be generalized to all the retailers in India since the study was conducted in Kanyakumari district, Tamilnadu.